Delegate Perspectives on Transitioning the 41st Canadian Symposium on Remote Sensing to a Virtual Event Due to the COVID-19 Pandemic. Issue 1 (2nd January 2022) - Hopkinson, Chris; Coburn, Craig A.
Abstract: The 41 st Canadian Symposium on Remote Sensing (CSRS) was a unique event, originally planned to be hosted as an in-person event in Yellowknife, Northwest Territories but ultimately delivered 100% online due to the COVID-19 global pandemic. As the 41 st CSRS represented an unprecedented departure from the CRSS-SCT's long history of annual in-person symposia, this note summarizes the transition from an in-person to an online event. In particular, delegate feedback on some of the challenges encountered, as well as positive and negative perceptions of the event delivery. It is important that a record of these collective experiences is preserved and considered for future symposia, and our experience is shared with the global research community.